Analysis of the Implementation of Small Medium Enterprise Cost of Production Price Study on Coffee Shop - Nur Abdi, Muhammad; Syamsuddin; Arfandi; Amran; Iksan Burnanuddin, Chairul (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2024)
Determination of good and appropriate production costs is one of the determining factors for determining the selling price of the product. The high and low cost of production will affect the level of sales. The purpose of this study is to analyse the determination of cost of goods based on activities at MSME Coffee Shop in Makassar, South Sulawesi. This research is important to determine whether determining the cost of goods using the activity-based costing method is appropriate without having to incur unnecessary costs and can provide benefits to these MSMEs. This type of research is descriptive research with a quantitative approach. The data used in this research is primary data. The data source used in this research is primary data in the form of data directly related to the Real Café beverage production process. In analyzing the data of this study, the stages in determining the cost of goods based on activity-based costing are as follows: first Factory overhead costs are charged to the appropriate activity. then Activity costs are grouped into homogeneous cost pools. then Determine the rate for each cost group. The rate is calculated by dividing the sum of all costs in the cost pool by the size of the activity performed. In the next stage, activity costs are charged to products based on the consumption or demand for the activity by each product. The results of this study indicate that Real Cafe has carried out the activity-based costing method in determining the cost of goods manufactured, characterized by the costs that arise are charged to activities and grouped into cost pools that have homogeneous properties, and the activity costs are charged to each product.